Disaggregated demand and policy analysis: The case of dairy demand in Mali - Debrah, S.K.; Sissoko, K.; Soumare, S. (1991)
A study carried out to estimate disaggregated demand parameters for dairy products and to use the results to illustrate the policy implications of dairy self-sufficient policy objectives on families in different income strata. Discusses patterns of dairy consumption in the sub-region with special emphasis on the dairy situation in Mali; describes the methodology and characteristics of sample households used in the analysis and presents the empirical model. Ends with a discussion on policy implications. Includes data on selected household characteristics and demand parameters by income category, and dairy demand equations.